Effect of genre-based approach on secondary school students’ achievement in English narrative writing in Toro LGA, Bauchi State - Usman , Ya’u; Muktar , M. Rabiu; Muhammad , A. Amin (Kashere Journal of Education, 2023)
This study was designed to determine the effects of genre-based approach on secondary school students’ achievement in narrative composition writing in Toro LGA, Bauchi State. The study adopted quasi-experimental research design consisting of two groups of SS 2 students, experimental and control. All conditions were similar in the two groups except that the students of the experimental group were exposed to the treatment of genre-based approach. Purposive sampling techniques of 79 SS2 students ware used. Narrative test instruction was adopted from past WAEC narrative questions which were administered at the end of series of narrative composition writing lessons. Data collected were analyzed using t-test statistics observed at 0.05 level of significance. The null hypotheses of no significant difference were tested and rejected while the alternate hypotheses were accepted. The result revealed that experimental group performed significantly better than the control group. This means that genre-based approach has a significant effect when taught narrative composition writing. It is therefore recommended that genre-based approach should be adopted in order to improve SS2 students’ achievement in narrative writing.